Clonal outbreak of an extensively drug-resistant NDM-1 producing Pseudomonas aeruginosa in a local hospital in the Czech Republic - Chudejova, Katerina; Sourenian, Tsolaire; Finianos, Marc; Sramkova, Anna; Papagiannitsis, Costas C; Hrabak, Jaroslav; Bitar, Ibrahim (Microbiology spectrum, 2026)
A clonal outbreak of 18 ST773 NDM-1 producing Pseudomonas aeruginosa strains has been detected for the first time in the Czech Republic. The strains were extremely drug-resistant (XDR) and resistant to serum killing. SNP-based phylogeny and CRISPR assay typing showed minimal genomic variations among the isolates. The results suggest a high-risk, persistent, virulent clone causing the hospital outbreak, with the possibility of a nationwide outbreak.IMPORTANCEOur research on the novel detection of the NDM-1 gene in carbapenem-resistant Pseudomonas aeruginosa ST773 in the Czech Republic is of great significance for public health and infection control. Until now, the emergence of this gene in P. aeruginosa strains was uncommon in this region, as carbapenem resistance was primarily associated with IMP and VIM types of MBLs. This nosocomial outbreak was triggered by an index case patient repatriated from areas with reported NDM-1 producing P. aeruginosa, illustrating how international travel contributes to the spread of such resistant pathogens. The results obtained in this study show that it is necessary to focus on tracing the source of infections to control and prevent nosocomial infections, helping to protect public health in the Czech Republic.
Keywords: Anti-Bacterial Agents; pseudomonádové infekce; Disease Outbreaks; ženské pohlaví; Microbial Sensitivity Tests; lidé; Česká republika; mikrobiální testy citlivosti; Cross Infection; infekce spojené se zdravotní péčí; antibakteriální látky; senioři; Carbapenems; beta-Lactamases; beta-laktamasy; Pseudomonas Infections; Aged; ST773; lidé středního věku; Humans; fylogeneze; nemocnice; Czech Republic; outbreak; blaNDM-1; karbapenemy; Pseudomonas aeruginosa; mužské pohlaví; mnohočetná bakteriální léková rezistence; Male; epidemický výskyt choroby; Hospitals; XDR; Middle Aged; Female; Phylogeny; Drug Resistance, Multiple, Bacterial